Psychometric properties and measurement invariance of the awareness of age-related change short form in older adult samples from Taiwan and Germany - Tseng, Han-Yun; Wu, Chi-Shin; Lee, Chun-Yi; Wu, I-Chien; Chang, Hsing-Yi; Hsu, Chih-Cheng; Hsiung, Chao Agnes; Kaspar, Roman; Wahl, Hans-Werner; Diehl, Manfred (The gerontologist, 2024)
This study examined the psychometric properties and measurement invariance of the 10-item Awareness of Age-Related Change Short Form (AARC-SF) questionnaire in a Chinese-speaking sample of older adults in Taiwan.Data from 292 participants (Mage = 77.64 years) in the Healthy Aging Longitudinal Study in Taiwan cohort were used for Study 1, whereas data from young-old adult samples in Germany were used for Study 2.Study 1 showed that the AARC-SF had satisfactory reliability and validity for assessing adults’ AARC in Taiwan. Analyses confirmed the 2-factor structure of AARC-gains and AARC-losses. Study 2 demonstrated strong measurement invariance across men and women, whereas direct comparisons of the item scores between young-old adults and old-old adults need to be made with caution. Noninvariance of loadings indicated that certain items were more closely linked to AARC-gains and AARC-losses in Taiwan than in Germany. Noninvariance of intercepts suggested potential biases in comparing item scores between Taiwanese and German older adults.The AARC-SF emerged as a reliable and valid instrument for capturing positive and negative subjective aging experiences among Taiwanese older adults. However, it is noteworthy that some items on the AARC-SF may solicit different responses from individuals of different ages and different countries of origin, requiring caution with age group and cross-cultural comparisons.
Online veröffentlicht: 29. Juni 2024
Gesehen am 23.06.2025